Comparative evaluation of use of reciprocating saw and bur in Le fort I osteotomy for superior repositioning of maxilla: A cross-sectional study - Shilpa S. Bawane; Pushkar P. Waknis; Prathamesh V. Bhujbal (Saudi Dental Journal)
Background: Traditionally bur has been used to carry out osteotomy. In a developing country like India, the cost of surgical treatment is the important factor in determining treatment plan. Although the use of bur is cost-effective and efficient, with the advent of newer technology, it is getting replaced with a saw. Aim: To evaluate and compare the use of reciprocating saw and bur in Le Fort I Osteotomy for superior repositioning of the maxilla. Materials and Methods: Patients referred from the Department of Orthodontics for the surgical correction of vertical maxillary excess (VME). They were divided into two groups. In group I, osteotomy was performed with Synthes Reciprocating Saw and in group II, bur was used. The parameters recorded in both the groups were time required for the completion of down-fracture, precision of the osteotomy cut (margins of the cut), and ease of superior repositioning. Data was collected from both the groups for comparison. Results: A total of 14 patients with VME were included in the study. They were divided into two groups. Seven study participants were allotted to each group. In group I, Synthes Reciprocating Saw was used while in group II, a bur was used to carry out the osteotomy cut. In group I, the average time required to complete the down-fracture of the maxilla was 3.5–4 min while in group II it was more than 8 min. The margins of the osteotomy cut were smooth and regular and there was bone-to-bone contact during superior repositioning in Group I. Conclusion: The combination of the use of a saw for inferior osteotomy and a bur for the superior cut would be more beneficial in the superior repositioning of the maxilla.